Kafka and noise : the discovery of cinematic sound in literary modernism - Gellen Norberg, Kata, 1978- (Northwestern University Press, 2019)
Kafka and Noise applies concepts from film theory and sound studies to explore noises in Kafka's writings--from Gregor Samsa's squeaking and Josefine the mouse singer's whistling to the terror of spoken Yiddish and the thrill of literary recitation.--Provided by publisher.